2017
DOI: 10.1186/s12889-017-4388-3
|View full text |Cite
|
Sign up to set email alerts
|

Working in dissonance: experiences of work instability in workers with common mental disorders

Abstract: BackgroundCommon mental disorders have a negative impact on work functioning, but less is known about the process when the functioning starts to destabilize. This study explores experiences of work instability in workers with common mental disorders.MethodsA grounded theory study using a theoretical sampling frame, individual in-depth interviews and a constant comparative analysis conducted by a multidisciplinary research team. The sample involved 27 workers with common mental disorders, currently working full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 49 publications
(73 reference statements)
2
38
0
1
Order By: Relevance
“…Comparing our results to previous research is challenging as most authors mainly analyzed factors that negatively impact the work life and focused on specific chronic health conditions [ 20 , 21 , 22 ]. In addition to that, most studies are single country studies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Comparing our results to previous research is challenging as most authors mainly analyzed factors that negatively impact the work life and focused on specific chronic health conditions [ 20 , 21 , 22 ]. In addition to that, most studies are single country studies.…”
Section: Discussionmentioning
confidence: 70%
“…The qualitative study of Danielsson and colleagues identified categories of negative impacts of common mental health conditions as unipolar depression or anxiety on work life based on individual interviews. The study explored experiences of instability in work-related functioning [ 21 ]. The most relevant category having a negative impact was the core category “Working in dissonance”.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with SED experienced emotional exposure when they entered the intervention and started to prepare for RTW. Experiences of exposure are complex among persons with SED and mental disorders, and may include personal views of vulnerability and self-blame [ 42 45 ], and societal views and stigma related to mental disorders, exhaustion and stress [ 12 , 46 ]. In addition, the high risk of long-term sickness absence due to SED and mental disorders may lead to marginalization because of job insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms are dominated by a substantial lack of mental energy, manifesting itself as lack of initiative, reduced stamina, or prolonged recovery after mental strain [ 1 ]. Work-related symptoms experienced by patients have recently been described as a sense of ‘work dissonance’, disrupted workflow, feeling out-of-sync, and social isolation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%